Implementasi Kegiatan Ekstrakurikuler Bahasa Inggris Dalam Meningkatkan Prestasi Siswa di MIN II Mojokerto: Implementation of English Extracurricular Activities in Improving Student Achievement at MIN II Mojokerto - Rahmat; Akhmad Fauzi (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
MIN II Mojokerto is a one of the schoils that implements extracurricular activities in English have become a platform for students to hone and maximize their talents, and intersts, as well as a platform for teachers to guide and nurture students in exploring their potencial further. The objectives of this research are: 1) to describe the planning of extracurricular activities in English to enhance students achievments, 2) to describe the implementation extracurricular activities in English to enhance students achievments, 3) to describe the obstacles or challengers in the implementation of extracurricular activities in English. In this research, a qualitative approach is used, employing a case study design. The research is conducted at MIN II Mojokerto school. Informants are selected trought pusposive sampling technique. Various methods are utilized to collect data, including observation, interviews and documentation. Meanwhile, data analysis is conducted using miles and huberman’s theory, involving data condensation, data validity is ensured through source triangulation and technique triangulation. The results of this research are as follows, 1) planning: a) Initiated by the vice principal for curriculum along with the coordinator and supervisor, b) extracurricular supervisors must have a background in English, c) participation is open to students from grades III to V, d) activities take place in the school hall, e) discussions between the ccordinator and the English extracurricular supervisor are held to discuss planning, f) activity scheduling is organized by the extracurricular coordinator. 2) implementation: a) activities commence from 6:20 t0 7:20 in the morning, b) conducted in the school hall, c) utilizes reading, writing, speaking and listening methods, d) media include powerpoint presentations, online websites, and videos, e) students participate in competitions at the district,and provincial levels. 3) challenges: a) sometimes used for teachers meetings, resulting in extracurricular activities being postponed, b) some students lack consistency in attendance, c) health issues pose a challenge, d) lack of class level distribution is hurdle. Keywords : Exracurrucular Activities in English, Student Achievment representative for the article